Both J- and L-shaped upper hemisternotomy approaches are suitable for total arch replacement with frozen elephant trunk in patients with Type A dissection - Yang, Zhonglu; Jiang, Hui; Liu, Yu; Ge, Yuguang; Wang, Huishan (Frontiers in Cardiovascular Medicine, 2022)
Background Minimally invasive total arch replacement (TAR) with frozen elephant trunk (FET) implantation can be carried out through J-, L-, and inverted T-shaped upper ministernotomy. L- and inverted T-shaped upper ministernotomy are selected mostly for their better surgical view compared to J-shaped. However, few studies have paid attention to the difference in clinical effects between J- and L-shaped upper hemisternotomy in acute Type A aortic dissection (ATAAD). Materials and methods We retrospectively analyzed 74 consecutive patients with ATAAD who underwent TAR with FET implantation between December 2019 and October 2020. Patients were divided into the L group (n = 31, L-shaped upper hemisternotomy) and the J group (n = 43, J-shaped upper hemisternotomy). Perioperative characteristics were recorded. Results No significant difference was found in any of the pre-operative, post-operative, or follow-up variables between the two groups. However, the CPB establishment time in the J group was significantly shorter than that in the L group (65.0 ± 17.9 min vs. 77.9 ± 17.2 min, P < 0.05). Other intraoperative variables showed no significant difference. Conclusion Total arch replacement with frozen elephant trunk implantation is feasible and can be carried out safely through J-shaped or L-shaped incision. A J-shaped incision might be beneficial for single incision, while an L-shaped incision might be beneficial if an extra incision is required to achieve better artery perfusion.